The role of edible insects to mitigate challenges for sustainability - Guiné Raquel P. F. (De Gruyter, 2021)
This review is focused on the utilization of insects as a new opportunity in food and feed products, including their commercialization both in traditional and new markets. It has been suggested that insects are considerably more sustainable when compared with other sources of animal protein, thus alleviating the pressure over the environment and the planet facing the necessity to feed the world population, constantly increasing. Many chefs have adhered to the trend of using insects in their culinary preparations, bringing insects to the plan of top gastronomy, highlighting their organoleptic qualities allied to a recognized high nutritional value. However, in some markets, insects or insect-based products are not readily accepted because of neophobia and disgust. Moreover, the insect markets, farming, and commercialization are experiencing a huge growth, in which the domain of animal feed is undoubtedly a very strong component. The future of insects as human food and animal feed seems promising in view of the recent trends and challenges.